Resin composition

By using a resin composition containing a specific maleimide compound and an active ester compound in the insulating layer of the printed circuit board, the problem of many shortcomings in the insulating layer performance in the prior art is solved, and an insulating layer with low dielectric constant, low dielectric loss, high glass transition temperature and excellent copper adhesion properties is achieved.

JP7665953B2Active Publication Date: 2025-04-22AJINOMOTO CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020188982
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-12
Publication Date
2025-04-22
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously realize the low relative dielectric constant (Dk), low dielectric loss (Df), high glass transition temperature (Tg) and excellent copper adhesion performance of the insulating layer of the printed circuit board.

Method used

A resin composition containing a specific maleimide compound and an active ester compound is used to form a high glass transition temperature insulating layer with low dielectric constant and dielectric loss, and the copper adhesion performance is improved.

Benefits of technology

The low relative dielectric constant and dielectric loss of the insulating layer, high glass transition temperature and excellent copper adhesion performance are achieved, and the multiple requirements of modern printed circuit board technology for the performance of the insulating layer are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665953000001
    Figure 0007665953000001
  • Figure 0007665953000002
    Figure 0007665953000002
  • Figure 0007665953000003
    Figure 0007665953000003
Patent Text Reader

Abstract

To provide a resin composition that can yield a cured product having low relative dielectric constant (Dk) and dielectric loss tangent (Df), high glass transition point (Tg), and excellent copper adhesion.SOLUTION: Provided is a resin composition that contains (A) a maleimide compound having a partial structure represented by the formula (A) (X1) (in the formula, each symbol is as described in the specification), and (B) an active ester compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a maleimide compound, and further to a cured product, a sheet-like laminate material, a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. [Background technology]

[0002] As a manufacturing technique for printed wiring boards, a manufacturing method using a build-up method in which insulating layers and conductor layers are alternately stacked is known. In the manufacturing method using the build-up method, the insulating layer is generally formed by curing a resin composition. In recent years, there has been a demand for further improvement in the dielectric properties of the insulating layer, such as the dielectric constant and the dielectric loss tangent, and further improvement in the copper adhesion. On the other hand, there has also been a demand for an insulating layer with a high glass transition temperature.

[0003] Various maleimide compounds containing a non-aromatic ring skeleton have been known so far (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-203122 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a resin composition which can give a cured product having a low relative dielectric constant (Dk) and dielectric dissipation factor (Df), a high glass transition point (Tg), and excellent copper adhesion. [Means for solving the problem]

[0006] Means for Solving the Problems of the Invention The present inventors conducted intensive studies in order to achieve the objects of the present invention and unexpectedly found that by using, as components of a resin composition, (A) a maleimide compound having a partial structure represented by formula (X1), and (B) an active ester compound, it is possible to obtain a cured product which has a low relative dielectric constant (Dk) and dielectric tangent (Df), a high glass transition point (Tg), and excellent copper adhesion, and thus completed the present invention.

[0007] That is, the present invention includes the following. [1] (A) Formula (X1):

[0008] [ka]

[0009] [In the formula, Ring X is an optionally substituted monocycloalkane ring or an optionally substituted monocycloalkene ring; a and b each independently represent 0, 1, 2, or 3, and the sum of a and b is 1 to 5; * indicates binding site.] and (B) an active ester compound. [2] The component (A) further comprises, in addition to the partial structure represented by formula (X1), the partial structure represented by formula (Y1):

[0010] [ka]

[0011] [In the formula, Ring Y represents a monocycloalkane ring which may be substituted, or a monocycloalkene ring which may be substituted; c and d each independently represent 0 or an integer of 1 or more, and the sum of c and d is 6 or more; * indicates binding site.] The resin composition according to the above [1], wherein the maleimide compound has a partial structure represented by the following formula: [3] The resin composition according to the above [1] or [2], wherein the number of maleimide groups in one molecule of the component (A) is 2. [4] The resin composition according to any one of the above [1] to [3], wherein the component (A) is a maleimide-terminated polyimide. [5] The component (A) is represented by the formula (A1):

[0012] [ka]

[0013] [In the formula, R 1 each independently represents a substituent; ring X and ring Y each independently represent a monocycloalkane ring which may have a substituent, or a monocycloalkene ring which may have a substituent; ring Z independently represents a non-aromatic ring which may have a substituent, or an aromatic ring which may have a substituent; Z 1 and Z 2 each independently represents a single bond, an alkylene group, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, -NHCO-, -COO-, or -OCO-; a and b each independently represent 0, 1, 2, or 3, and the sum of a and b is 1 to 5; c and d each independently represent 0 or an integer of 1 or more, and the sum of c and d is 6 or more; e each independently represents 0 or 1; Each f independently represents an integer of 0 or 1 or more; Each g independently represents 0, 1, or 2; n1 represents an integer equal to or greater than 1; n2 represents an integer of 0 or 1 or more; One of m1 and m2 represents 1 and the other represents 0.] The resin composition according to any one of the above [1] to [4], wherein the compound is represented by the following formula: [6] The resin composition according to any one of the above [1] to [5], wherein the weight average molecular weight of the component (A) is 2,000 to 50,000. [7] The resin composition according to any one of the above [1] to [6], wherein the content of the component (A) is 3% by mass to 30% by mass, based on 100% by mass of the non-volatile components in the resin composition. [8] The resin composition according to any one of the above [1] to [7], wherein the content of the component (B) is 3% by mass to 30% by mass, based on 100% by mass of the non-volatile components in the resin composition. [9] The resin composition according to any one of the above [1] to [8], wherein a mass ratio of the component (A) to the component (B) (component (A) / component (B)) is 0.5 to 3.

[10] The resin composition according to any one of the above [1] to [9], further comprising (C) an epoxy resin.

[11] The resin composition according to any one of the above [1] to

[10] , further comprising (D) an inorganic filler.

[12] The resin composition according to

[11] above, wherein the content of the (D) component is 40 mass% or more, based on 100 mass% of the non-volatile components in the resin composition.

[13] The resin composition according to any one of the above [1] to

[12] , wherein a dielectric loss tangent (Df) of a cured product of the resin composition is 0.005 or less when measured at 5.8 GHz and 23°C.

[14] The resin composition according to any one of the above [1] to

[13] , wherein a cured product of the resin composition has a relative dielectric constant (Dk) of 3.0 or less when measured at 5.8 GHz and 23°C.

[15] The resin composition according to any one of the above [1] to

[14] , wherein the glass transition temperature (Tg) of a cured product of the resin composition is 150° C. or higher.

[16] A cured product of the resin composition according to any one of [1] to

[15] above.

[17] A sheet-like laminate material comprising the resin composition according to any one of the above [1] to

[15] .

[18] A resin sheet comprising: a support; and a resin composition layer formed on the support, the resin composition being formed from the resin composition according to any one of [1] to

[15] above.

[19] A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of [1] to

[15] above.

[20] A semiconductor device comprising the printed wiring board described in

[19] above. Effect of the Invention

[0014] According to the resin composition of the present invention, it is possible to obtain a cured product which has a low relative dielectric constant (Dk) and dielectric dissipation factor (Df), a high glass transition point (Tg), and excellent copper adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0016] <Resin composition> The resin composition of the present invention is represented by formula (A) (X1):

[0017] [ka]

[0018] [In the formula, ring X represents a monocycloalkane ring which may have a substituent, or a monocycloalkene ring which may have a substituent; a and b each independently represent 0, 1, 2, or 3, and the sum of a and b is 1 to 5; and * represents a bonding site.] and (B) an active ester compound. By using such a resin composition, it is possible to obtain a cured product having a low relative dielectric constant (Dk) and dielectric loss tangent (Df), a high glass transition point (Tg), and excellent copper adhesion.

[0019] The resin composition of the present invention may further contain optional components in addition to the specific maleimide compound (A) and the active ester compound (B). Examples of the optional components include other radical polymerizable compounds (A'), epoxy resins (C), inorganic fillers (D), curing accelerators (E), other additives (F), and organic solvents (G). Each component contained in the resin composition will be described in detail below.

[0020] <(A) Specific Maleimide Compound> The resin composition of the present invention contains (A) a specific maleimide compound. The maleimide compound means a compound containing at least one maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group) in one molecule. The number of maleimide groups in one molecule of (A) the specific maleimide compound is preferably 2 or more, and particularly preferably 2. The (A) specific maleimide compound may be used alone or in combination of two or more at any ratio.

[0021] (A) The specific maleimide compound has the formula (X1):

[0022] [ka]

[0023] [In the formula, ring X represents a monocycloalkane ring which may have a substituent, or a monocycloalkene ring which may have a substituent; a and b each independently represent 0, 1, 2, or 3, and the sum of a and b is 1 to 5; and * represents a bonding site.] It has a partial structure represented by the following formula:

[0024] Ring X is an optionally substituted monocycloalkane ring or an optionally substituted monocycloalkene ring.

[0025] The monocycloalkane ring means a monocyclic aliphatic saturated hydrocarbon ring. The monocycloalkane ring is preferably a monocycloalkane ring having 4 to 14 carbon atoms, more preferably a monocycloalkane ring having 4 to 10 carbon atoms, and particularly preferably a monocycloalkane ring having 5 or 6 carbon atoms. Examples of the monocycloalkane ring include a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring. The cycloalkene ring means a monocyclic aliphatic unsaturated hydrocarbon ring having at least one carbon-carbon double bond. The monocycloalkene ring is preferably a monocycloalkene ring having 4 to 14 carbon atoms, more preferably a monocycloalkene ring having 4 to 10 carbon atoms, and particularly preferably a monocycloalkene ring having 5 or 6 carbon atoms. Examples of the monocycloalkene ring include a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, a cyclooctene ring, a cyclopentadiene ring, and a cyclohexadiene ring.

[0026] In the present specification, the term "substituent" is not particularly limited, and examples thereof include monovalent substituents such as an alkyl group, an alkenyl group, an aryl group, an aryl-alkyl group (an alkyl group substituted with an aryl group), an alkyl-oxy group, an alkenyl-oxy group, an aryl-oxy group, an alkyl-carbonyl group, an alkenyl-carbonyl group, an aryl-carbonyl group, an alkyl-oxy-carbonyl group, an alkenyl-oxy-carbonyl group, an aryl-oxy-carbonyl group, an alkyl-carbonyl-oxy group, an alkenyl-carbonyl-oxy group, and an aryl-carbonyl-oxy group, and may also include divalent substituents such as an oxo group (=O) if substitutable.

[0027] The alkyl group means a linear, branched and / or cyclic monovalent aliphatic saturated hydrocarbon group. The alkyl group is preferably an alkyl group having 1 to 14 carbon atoms, unless otherwise specified. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a cyclopentyl group, a cyclohexyl group, a methylcyclohexyl group, a dimethylcyclohexyl group, a trimethylcyclohexyl group, a cyclopentylmethyl group, and a cyclohexylmethyl group. The alkenyl group means a linear, branched and / or cyclic monovalent aliphatic unsaturated hydrocarbon group having at least one carbon-carbon double bond. The alkenyl group is preferably an alkenyl group having 2 to 14 carbon atoms, unless otherwise specified. Examples of the alkenyl group include vinyl, propenyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, and cyclohexenyl groups. The aryl group means a monovalent aromatic hydrocarbon group. Unless otherwise specified, the aryl group is preferably an aryl group having 6 to 14 carbon atoms. Examples of the aryl group include a phenyl group, a 1-naphthyl group, and a 2-naphthyl group.

[0028] Ring X is preferably a monocycloalkane ring which may be substituted with a group selected from an alkyl group and an alkenyl group, or a monocycloalkene ring which may be substituted with a group selected from an alkyl group and an alkenyl group. Ring X is more preferably a monocycloalkane ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 6 carbon atoms and an alkenyl group having 1 to 6 carbon atoms, or a monocycloalkene ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 6 carbon atoms and an alkenyl group having 1 to 6 carbon atoms. Ring X is more preferably a monocycloalkane ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 6 carbon atoms. Ring X is particularly preferably a cyclohexane ring which may be substituted with a methyl group.

[0029] a and b each independently represent 0, 1, 2 or 3, and the sum of a and b is 1 to 5. a and b each preferably independently represent 0, 1 or 2, and the sum of a and b is 1 or more. a and b each more preferably independently represent 0 or 1, and the sum of a and b is 1 or more. It is particularly preferred that one of a and b is 1 and the other is 0.

[0030] The partial structure represented by formula (X1) is preferably represented by formula (X2):

[0031] [ka]

[0032] [In the formula, R 2 each independently represents an alkyl group; x represents an integer of 0 to 5; and other symbols are as defined above.] It is a partial structure represented by:

[0033] R 2 R each independently represents an alkyl group. 2 are each independently preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group. x represents an integer of 0 to 5. x is preferably 0, 1, 2, 3 or 4, more preferably 1, 2, 3 or 4, further preferably 2, 3 or 4, and particularly preferably 3.

[0034] The partial structure represented by formula (X1) is particularly preferably represented by formula (X3):

[0035] [ka]

[0036] [In the formula, * is the same as above.] It is a partial structure represented by:

[0037] The number of the partial structure represented by formula (X1) in one molecule of the (A) specific maleimide compound is at least 1, and preferably 2 or more, and the upper limit can be, for example, 20 or less, 10 or less, etc.

[0038] The specific maleimide compound (A) preferably further comprises, in addition to the partial structure represented by formula (X1), a partial structure represented by formula (Y1):

[0039] [ka]

[0040] [In the formula, ring Y represents a monocycloalkane ring which may have a substituent, or a monocycloalkene ring which may have a substituent; c and d each independently represent an integer of 0 or 1 or more, and the sum of c and d is 6 or more; and * represents a bonding site.] It has a partial structure represented by the following formula:

[0041] Ring Y represents a monocycloalkane ring which may have a substituent, or a monocycloalkene ring which may have a substituent. Ring Y is preferably a monocycloalkane ring which may be substituted with a group selected from an alkyl group and an alkenyl group, or a monocycloalkene ring which may be substituted with a group selected from an alkyl group and an alkenyl group. Ring Y is more preferably a monocycloalkane ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 14 carbon atoms and an alkenyl group having 1 to 14 carbon atoms, or a monocycloalkene ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 14 carbon atoms and an alkenyl group having 1 to 14 carbon atoms. Ring Y is more preferably a monocycloalkane ring having 4 to 10 carbon atoms which may be substituted with a group selected from an alkyl group having 1 to 14 carbon atoms. Ring Y is particularly preferably a cyclohexane ring which may be substituted with a group selected from an alkyl group having 4 to 10 carbon atoms.

[0042] c and d each independently represent an integer of 0 or 1 or more, and the sum of c and d is 6 or more. c and d each preferably independently represent an integer of 0 to 20, and the sum of c and d is 6 or more. c and d each more preferably independently represent an integer of 1 to 20, and the sum of c and d is 6 or more. c and d each more preferably independently represent an integer of 5 to 10. c and d are particularly preferably 8.

[0043] The partial structure represented by formula (Y1) is preferably represented by formula (Y2):

[0044] [ka]

[0045] [In the formula, R 3 each independently represents an alkyl group; y represents an integer of 0 to 5; and other symbols are as defined above.] It is a partial structure represented by:

[0046] R 3 R each independently represents an alkyl group. 3 are each independently preferably an alkyl group having 1 to 14 carbon atoms, more preferably an alkyl group having 4 to 10 carbon atoms, and particularly preferably an alkyl group having 6 to 8 carbon atoms. y represents an integer of 0 to 5. y is preferably 0, 1, 2, 3 or 4, more preferably 1, 2, 3 or 4, further preferably 1, 2 or 3, and particularly preferably 2.

[0047] The partial structure represented by formula (Y1) is particularly preferably represented by formula (Y3):

[0048] [ka]

[0049] [In the formula, * is the same as above.] It is a partial structure represented by:

[0050] The number of the partial structure represented by formula (Y1) in one molecule of the specific maleimide compound (A) is at least 1, and preferably 2 or more, and the upper limit can be, for example, 20 or less, 10 or less, etc.

[0051] In one embodiment, the specific maleimide compound (A) is preferably a maleimide-terminated polyimide. A maleimide-terminated polyimide is a chain polyimide (a chain polymer containing an imide structure in a repeating unit) having maleimide groups at both ends. It is known that a maleimide-terminated polyimide can be obtained, for example, by imidization reaction of a component containing a diamine compound, maleic anhydride, and tetracarboxylic dianhydride.

[0052] (A) In one embodiment, the specific maleimide compound has the formula (n1):

[0053] [ka]

[0054] [In the formula, R 1 each independently represents a substituent; each Z ring independently represents a non-aromatic ring which may have a substituent, or an aromatic ring which may have a substituent; Z 1 and Z 2 each independently represents a single bond, an alkylene group, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, -NHCO-, -COO-, or -OCO-; each independently represents 0 or 1; each independently represents an integer of 0 or 1 or more; each independently represents 0, 1, or 2; and the other symbols are the same as above. In addition to the structural unit represented by formula (n1), it is preferable that the maleimide compound further contains a structural unit represented by formula (n2):

[0055] [ka]

[0056] [In the formula, each symbol is as defined above.] It is more preferable that the maleimide compound contains a structural unit represented by the following formula: The f units and g units may be the same or different for each unit.

[0057] R 1 each independently represents a substituent, preferably an alkyl group. Each Z ring independently represents a non-aromatic ring which may have a substituent, or an aromatic ring which may have a substituent, preferably an aromatic ring which may have a substituent.

[0058] The aromatic ring means a ring conforming to the Huckel rule in which the number of electrons contained in the π electron system on the ring is 4p+2 (p is a natural number). The aromatic ring may be an aromatic carbocycle having a carbon atom as a ring-constituting atom, or an aromatic heterocycle having a heteroatom such as an oxygen atom, a nitrogen atom, or a sulfur atom in addition to a carbon atom as a ring-constituting atom, but in one embodiment, it is preferably an aromatic carbocycle. In one embodiment, the aromatic ring is preferably a 5-14-membered aromatic ring, more preferably a 5-10-membered aromatic ring, and even more preferably a 5- or 6-membered aromatic ring. Suitable specific examples of the aromatic ring include a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, and the like, more preferably a benzene ring or a naphthalene ring, and particularly preferably a benzene ring.

[0059] The non-aromatic ring means a ring other than an aromatic ring. The non-aromatic ring may be a non-aromatic carbocycle having a carbon atom as a ring-constituting atom, or a non-aromatic heterocycle having a heteroatom such as an oxygen atom, a nitrogen atom, or a sulfur atom in addition to a carbon atom as a ring-constituting atom, but in one embodiment, it is preferably a non-aromatic carbocycle. The non-aromatic ring may be a saturated ring or an unsaturated non-aromatic ring, but in one embodiment, it is preferably a saturated ring. In one embodiment, the non-aromatic ring is preferably a 4-14-membered non-aromatic ring. Examples of the non-aromatic ring include monocycloalkane rings such as a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring; monocycloalkene rings such as a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, a cyclooctene ring, a cyclopentadiene ring, and a cyclohexadiene ring; and aromatic ring-non-aromatic ring condensed rings such as an indane ring, an indene ring, a tetralin ring, and a fluorene ring.

[0060] Z 1 and Z 2 each independently represents a single bond, an alkylene group, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, -NHCO-, -COO-, or -OCO-.

[0061] The alkylene group refers to a linear or branched divalent aliphatic saturated hydrocarbon group. The alkylene group is preferably an alkylene group having 1 to 14 carbon atoms. Examples of the alkylene group include linear alkylene groups such as methylene, ethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, and decamethylene; and branched alkylene groups such as ethylidene (-CH(CH3)-), propylidene (-CH(CH2CH3)-), isopropylidene (-C(CH3)2-), ethylmethylmethylene (-C(CH3)(CH2CH3)-), and diethylmethylene (-C(CH2CH3)2-).

[0062] e represents 0 or 1, and is preferably 0. f each independently represents 0 or an integer of 1 or more, and is preferably 0, 1, or 2. g each independently represents 0, 1, or 2, and is preferably 0.

[0063] The partial structure represented by formula (X1) contained in the structural unit represented by formula (n1) is preferably a partial structure represented by formula (X2), and more preferably a partial structure represented by formula (X3). The partial structure represented by formula (Y1) contained in the structural unit represented by formula (n2) is preferably a partial structure represented by formula (Y2), and more preferably a partial structure represented by formula (Y3).

[0064] The structural units represented by the formulas (n1) and (n2) include the formula (Z):

[0065] [ka]

[0066] [In the formula, * is the same as above.] Specific examples of the partial structure represented by the formulas (Z-1) to (Z-25):

[0067] [ka]

[0068] [In the formula, * is the same as above.] Among these, the partial structure represented by formula (Z-1) is preferable.

[0069] In one embodiment, the specific maleimide compound (A) is more preferably represented by formula (A1):

[0070] [ka]

[0071] [In the formula, n1 represents an integer of 1 or more; n2 represents 0 or an integer of 1 or more (preferably an integer of 1 or more); one of m1 and m2 represents 1 and the other represents 0; and other symbols are the same as above.] (there is a bond between the n1 unit and the n2 unit). The order and individual arrangement of the n1 unit and the n2 unit are arbitrary, and include alternating copolymers, block copolymers, random copolymers, etc. The n1 unit and the n2 unit may be the same or different for each unit.

[0072] The partial structure represented by formula (X1) contained in the compound represented by formula (A1) is preferably a partial structure represented by formula (X2), and more preferably a partial structure represented by formula (X3). The partial structure represented by formula (Y1) contained in the compound represented by formula (A1) is preferably a partial structure represented by formula (Y2), and more preferably a partial structure represented by formula (Y3). The partial structure represented by formula (Z) contained in the compound represented by formula (A1) is preferably a partial structure represented by formula (Z-1).

[0073] (A) In one embodiment, the specific maleimide compound is even more preferably represented by formula (A2):

[0074] [ka]

[0075] [In the formula, each symbol is as defined above.] (n1 unit and n2 unit are connected by a bond), and particularly preferably, a compound represented by formula (A3):

[0076] [ka]

[0077] [In the formula, each symbol is as defined above.] (there is a bond between the n1 unit and the n2 unit).

[0078] The weight average molecular weight (Mw) of the (A) specific maleimide compound is preferably 1000 to 50000, more preferably 2000 to 50000, more preferably 2000 to 40000, and even more preferably 2500 to 20000. The number average molecular weight (Mn) of the (A) specific maleimide compound is preferably 1000 to 50000, more preferably 1500 to 40000, and even more preferably 2000 to 20000. The weight average molecular weight and number average molecular weight of the resin can be measured as polystyrene-equivalent values ​​by gel permeation chromatography (GPC).

[0079] The functional group equivalent of the (A) specific maleimide compound is preferably 500 g / eq. to 20000 g / eq., more preferably 1000 g / eq. to 10000 g / eq. The functional group equivalent of the (A) specific maleimide compound is the mass of the (A) specific maleimide compound per equivalent of maleimide group.

[0080] An example of a commercially available product of the (A) specific maleimide compound is “SLK-2600” manufactured by Shin-Etsu Chemical Co., Ltd.

[0081] The content of the (A) specific maleimide compound in the resin composition is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. The lower limit of the content of the (A) specific maleimide compound in the resin composition is not particularly limited, but is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0082] <(A') Other radical polymerizable compounds> The resin composition of the present invention may further contain, as an optional component, (A') a radically polymerizable compound other than the component (A). The (A') radically polymerizable compound may be used alone or in any combination of two or more kinds.

[0083] The radical polymerizable compound (A') may be, for example, a compound having a radical polymerizable unsaturated group. The radical polymerizable unsaturated group is not particularly limited as long as it is radical polymerizable, but is preferably an ethylenically unsaturated group having a carbon-carbon double bond at the end or inside, specifically, an unsaturated aliphatic group such as an allyl group or a 3-cyclohexenyl group; an unsaturated aliphatic group-containing aromatic group such as a p-vinylphenyl group, a m-vinylphenyl group, or a styryl group; an α,β-unsaturated carbonyl group such as an acryloyl group, a methacryloyl group, a maleoyl group (maleimide group when imidized), or a fumaroyl group. The radical polymerizable compound (A') preferably has one or more radical polymerizable unsaturated groups, more preferably has two or more radical polymerizable unsaturated groups.

[0084] As the (A') other radically polymerizable compound, a wide variety of known radically polymerizable compounds can be used, and there is no particular limitation thereon. Examples of such compounds include maleimide-based radically polymerizable compounds having two or more maleimide groups other than the component (A), vinylphenyl-based radically polymerizable compounds having two or more vinylphenyl groups, and (meth)acrylic-based radically polymerizable compounds having two or more acryloyl groups and / or methacryloyl groups.

[0085] The maleimide radical polymerizable compound is not particularly limited, and may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Commercially available products include, for example, "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (dimer diamine structure-containing maleimide compounds) manufactured by Designer Molecules, Inc., "BMI-6100" (aromatic maleimide compound) manufactured by Designer Molecules, "MIR-5000-60T" and "MIR-3000-70MT" (biphenylaralkyl-type maleimide compounds) manufactured by Nippon Kayaku Co., Ltd., "BMI-70" and "BMI-80" manufactured by K.I. Kasei Co., Ltd., and "BMI-2300" and "BMI-TMH" manufactured by Daiwa Kasei Kogyo Co., Ltd. In addition, as the maleimide-based radically polymerizable compound, a maleimide resin (maleimide compound containing an indane ring skeleton) disclosed in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 may be used.

[0086] The vinylphenyl radical polymerizable compound is not particularly limited, but in one embodiment, it is preferably a thermoplastic resin having a vinylphenyl group, more preferably a resin selected from modified polyphenylene ether resins having a vinylphenyl group and modified polystyrene resins having a vinylphenyl group. Commercially available products include, for example, "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Company, Inc.; "ODV-XET-X03", "ODV-XET-X04", and "ODV-XET-X05" (divinylbenzene / styrene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd.

[0087] The (meth)acrylic radical polymerizable compound is not particularly limited, but in one embodiment, it is preferably a thermoplastic resin having an acryloyl group and / or a methacryloyl group, and more preferably a resin selected from a modified polyphenylene ether resin having an acryloyl group and / or a methacryloyl group, and a modified polystyrene resin having an acryloyl group and / or a methacryloyl group. Examples of commercially available products include "SA9000" and "SA9000-111" (methacrylic modified polyphenylene ether resins) manufactured by SABIC Innovative Plastics.

[0088] The functional group equivalent of the (A') other radical polymerizable compound is preferably 100 g / eq. to 20000 g / eq., more preferably 200 g / eq. to 15000 g / eq., and further preferably 300 g / eq. to 10000 g / eq. The functional group equivalent of the (A') other radical polymerizable compound is the mass of the (A') other radical polymerizable compound per equivalent of the radical polymerizable unsaturated group (i.e., maleimide group, vinylphenyl group, acryloyl group, methacryloyl group, etc.).

[0089] The weight average molecular weight (Mw) of the (A') other radical polymerizable compound is preferably 500 to 50,000, more preferably 700 to 20,000. The number average molecular weight (Mn) of the (A') other radical polymerizable compound is preferably 500 to 50,000, more preferably 700 to 20,000.

[0090] The content of the (A') other radical polymerizable compound in the resin composition is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 10% by mass or less, when the non-volatile components in the resin composition are 100% by mass. The lower limit of the content of the (A') other radical polymerizable compound in the resin composition is not particularly limited, but may be, for example, 0% by mass or more, 0.1% by mass or more, 1% by mass or more, 2% by mass or more, when the non-volatile components in the resin composition are 100% by mass.

[0091] The content of the specific maleimide compound (A) in the resin composition is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and particularly preferably 50% by mass or more, when the total amount of radically polymerizable compounds in the resin composition (the sum of the components (A) and (A')) is taken as 100% by mass.

[0092] <(B) Active ester compound> The resin composition of the present invention contains an active ester compound (B). The active ester compound (B) may be used alone or in combination of two or more at any ratio. In one embodiment, when the resin composition contains an epoxy resin (C) or when the resin composition is mixed with an epoxy resin (C), the active ester compound (B) may function as an epoxy resin curing agent that reacts with the epoxy resin (C) to cure it.

[0093] As the (B) active ester compound, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0094] Specifically, the (B) active ester compound is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, or an active ester compound containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound, and even more preferably a dicyclopentadiene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.

[0095] (B) Commercially available active ester compounds include, as active ester compounds containing a dicyclopentadiene-type diphenol structure, "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", "HPC-8000H-65TM" (manufactured by DIC Corporation); as active ester compounds containing a naphthalene structure, "EXB-8100L-65T", "EXB-8150-60T", "EXB-8150-62T", Examples of the active ester compound containing phosphorus include "EXB9401" (manufactured by DIC Corporation), "DC808" (manufactured by Mitsubishi Chemical Corporation) which is an active ester compound that is an acetylated product of phenol novolac, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) which are active ester compounds that are benzoylated products of phenol novolac, and "PC1300-02-65MA" (manufactured by Air Water Corporation) which is an active ester compound containing a styryl group and a naphthalene structure.

[0096] The active ester group equivalent of the (B) active ester compound is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and further preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of the active ester compound per equivalent of the active ester group.

[0097] The content of the (B) active ester compound in the resin composition is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. The lower limit of the content of the (B) active ester compound in the resin composition is not particularly limited, but is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0098] The mass ratio of the specific maleimide compound (A) to the active ester compound (B) in the resin composition (component (A) / component (B)) is preferably 0.1 or more, more preferably 0.5 or more, and particularly preferably 0.7 or more. The upper limit of the mass ratio of the specific maleimide compound (A) to the active ester compound (B) in the resin composition (component (A) / component (B)) is preferably 10 or less, more preferably 3 or less, and particularly preferably 1.5 or less.

[0099] <(C) Epoxy resin> The resin composition of the present invention may contain an epoxy resin (C) as an optional component. The epoxy resin (C) is a curable resin having an epoxy group.

[0100] (C) Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, and glycidyl ester type epoxy resins. Examples of the epoxy resins include cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalimidine type epoxy resins, phenolphthalein type epoxy resins, etc. (C) The epoxy resins may be used alone or in combination of two or more.

[0101] The resin composition preferably contains, as the epoxy resin (C), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin (C) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0102] Epoxy resins include epoxy resins that are liquid at a temperature of 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resins as epoxy resins, or may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins. The epoxy resin in the resin composition of the present invention is preferably a solid epoxy resin or a combination of a liquid epoxy resin and a solid epoxy resin, and more preferably a solid epoxy resin.

[0103] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0104] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred.

[0105] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; and "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation. glycidylamine type epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type epoxy resin); Nippon Steel Chemical & Material Chemical's "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase Chemtex's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton); Daicel's "PB-3600", Nippon Soda's "JP-100" and "JP-200" (epoxy resin having a butadiene structure); Nippon Steel Chemical & Material Chemical's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc. These may be used alone or in combination of two or more types.

[0106] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0107] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, phenolphthalimidine type epoxy resins, and phenolphthalein type epoxy resins.

[0108] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-7311" manufactured by DIC Corporation. , "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", "ESN4 100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y Examples of epoxy resins include "X7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.

[0109] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (C) epoxy resin, the mass ratio of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin / solid epoxy resin) is not particularly limited, but is preferably 10 or less, more preferably 5 or less, even more preferably 1 or less, still more preferably 0.5 or less, and particularly preferably 0.1 or less.

[0110] The epoxy equivalent of the (C) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0111] The weight average molecular weight (Mw) of the epoxy resin (C) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0112] The content of the epoxy resin (C) in the resin composition is not particularly limited, but is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. The lower limit of the content of the epoxy resin (C) in the resin composition is not particularly limited, but is, for example, 0% by mass or more, preferably 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, even more preferably 5% by mass or more, and particularly preferably 10% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0113] The mass ratio of the specific maleimide compound (A) to the epoxy resin (C) in the resin composition (component (A) / component (C)) is preferably 0.1 or more, more preferably 0.3 or more, and particularly preferably 0.5 or more. The upper limit of the mass ratio of the specific maleimide compound (A) to the epoxy resin (C) in the resin composition (component (A) / component (C)) is preferably 10 or less, more preferably 3 or less, and particularly preferably 1 or less.

[0114] <(D) Inorganic filler> The resin composition of the present invention may contain an inorganic filler (D) as an optional component. The inorganic filler (D) is contained in the resin composition in the form of particles.

[0115] (D) An inorganic compound is used as the material of the inorganic filler. (D) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (D) inorganic filler may be used alone or in combination of two or more kinds in any ratio.

[0116] (D) Commercially available inorganic fillers include, for example, "UFP-30" manufactured by Denka Chemical Industry Co., Ltd.; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; and "DAW-03" and "FB-105FD" manufactured by Denka Company, Ltd.

[0117] The average particle size of the (D) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 2 μm or less, even more preferably 1 μm or less, and particularly preferably 0.7 μm or less. The lower limit of the average particle size of the (D) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (D) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0118] The specific surface area of ​​the (D) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the inorganic filler (D) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0119] The inorganic filler (D) is preferably surface-treated with an appropriate surface treatment agent, which can enhance the moisture resistance and dispersibility of the inorganic filler (D). Examples of the surface treatment agent include vinyl-based silane coupling agents such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy-based silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; styryl-based silane coupling agents such as p-styryltrimethoxysilane; methacryl-based silane coupling agents such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane; acrylic-based silane coupling agents such as 3-acryloxypropyltrimethoxysilane; N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, and N-2-(aminoethyl)-3-aminopropyltriethoxysilane; Amino-based silane coupling agents such as trimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-8-aminooctyltrimethoxysilane, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane; isocyanurate-based silane coupling agents such as tris-(trimethoxysilylpropyl)isocyanurate; ureido-based silane coupling agents such as 3-ureidopropyltrialkoxysilane; mercapto-based silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate-based silane coupling agents such as 3-isocyanatepropyltriethoxysilane; acid anhydride-based silane coupling agents such as 3-trimethoxysilylpropylsuccinic anhydride; and other silane coupling agents;Examples of the surface treatment agent include alkylalkoxysilane compounds such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, and trifluoropropyltrimethoxysilane. The surface treatment agent may be used alone or in combination of two or more in any ratio.

[0120] Commercially available surface treatment agents include, for example, "KBM-1003" and "KBE-1003" (vinyl-based silane coupling agents), "KBM-303", "KBM-402", "KBM-403", "KBE-402", and "KBE-403" (epoxy-based silane coupling agents), "KBM-1403" (styryl-based silane coupling agents), "KBM-502", "KBM-503", "KBE-502", and "KBE-503" (methacrylic-based silane coupling agents), "KBM-5103" (acrylic-based silane coupling agents), "KBM-602", "KBM-603", "KBM-903", "KBE-903", "KBE-9103P", "KBM-573", and "KBM-575" (amino-based silane coupling agents), all of which are manufactured by Shin-Etsu Chemical Co., Ltd. coupling agent); "KBM-9659" (isocyanurate-based silane coupling agent); "KBE-585" (ureido-based silane coupling agent); "KBM-802", "KBM-803" (mercapto-based silane coupling agent); "KBE-9007N" (isocyanate-based silane coupling agent); "X-12-967C" (acid anhydride-based silane coupling agent); "KBM-13", "KBM-22", "KBM-103", "KBE-13", "KBE-22", "KBE-103", "KBM-3033", "KBE-3033", "KBM-3063", "KBE-3063", "KBE-3083", "KBM-3103C", "KBM-3066", "KBM-7103" (alkylalkoxysilane compound), and the like.

[0121] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.

[0122] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0123] (D) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0124] The content of the (D) inorganic filler in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it may be preferably 90 mass% or less, more preferably 80 mass% or less, even more preferably 75 mass% or less, and particularly preferably 70 mass% or less. The lower limit of the content of the (D) inorganic filler in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it may be, for example, 0 mass% or more, 1 mass% or more, etc., preferably 10 mass% or more, more preferably 30 mass% or more, even more preferably 40 mass% or more, and particularly preferably 50 mass% or more.

[0125] The mass ratio of the specific maleimide compound (A) to the inorganic filler (D) in the resin composition (component (A) / component (D)) is preferably 0.01 or more, more preferably 0.05 or more, and particularly preferably 0.1 or more. The upper limit of the mass ratio of the specific maleimide compound (A) to the inorganic filler (D) in the resin composition (component (A) / component (D)) is preferably 1 or less, more preferably 0.5 or less, and particularly preferably 0.3 or less.

[0126] <(E) Curing accelerator> The resin composition of the present invention may contain a curing accelerator (E) as an optional component. In one embodiment, when the resin composition contains an epoxy resin (C) or when the resin composition is mixed with an epoxy resin (C), the curing accelerator (E) has a function of accelerating the curing of the epoxy resin (C).

[0127] Examples of the curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. Among them, imidazole-based curing accelerators are preferred from the viewpoint of improving crosslinking properties. (E) The curing accelerator may be used alone or in combination of two or more.

[0128] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0129] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0130] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0131] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.

[0132] As the imidazole-based curing accelerator, commercially available products may be used, for example, "1B2PZ", "2MZA-PW", and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0133] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0134] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.

[0135] As the amine-based curing accelerator, a commercially available product may be used, for example, "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0136] The content of the (E) curing accelerator in the resin composition is not particularly limited, but is preferably 15% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 3% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. The lower limit of the content of the (E) curing accelerator in the resin composition is not particularly limited, but may be, for example, 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, 0.1% by mass or more, 0.5% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0137] <(F) Other additives> The resin composition of the present invention may further contain any additive as a non-volatile component. Examples of such additives include radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; epoxy curing agents other than active ester compounds such as phenol curing agents, acid anhydride curing agents, thiol curing agents, benzoxazine curing agents, cyanate ester curing agents, carbodiimide curing agents, imidazole curing agents, and amine curing agents; thermoplastic resins such as phenoxy resins, polyvinyl acetal resins, polyolefin resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyether ether ketone resins, and polyester resins; organic fillers such as rubber particles; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; and ventilated resins. thickeners such as silane, montmorillonite, etc.; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, vinyl resin-based defoamers, etc.; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers, etc.; adhesion improvers such as urea silane, etc.; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, triazine-based adhesion imparters, etc.; antioxidants such as hindered phenol-based antioxidants, etc.; fluorescent brighteners such as stilbene derivatives, etc.; surfactants such as fluorine-based surfactants, silicone-based surfactants, etc.; phosphorus-based flame retardants (for example, phosphate ester compounds flame retardants such as inorganic flame retardants (e.g., antimony trioxide), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers.The (F) other additives may be used alone or in any combination of two or more kinds at any ratio. The content of the (F) other additives can be appropriately determined by a person skilled in the art.

[0138] <(G) Organic solvent> The resin composition of the present invention may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. As the (G) organic solvent, a known one can be appropriately used, and the type is not particularly limited. As the (G) organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methoxypropionic acid, etc. Examples of the organic solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent (G) may be used alone or in combination of two or more in any ratio.

[0139] In one embodiment, the content of the (G) organic solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, etc.

[0140] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by adding (A) a specific maleimide compound, (B) an active ester compound, if necessary (A') other radical polymerizable compounds, if necessary (C) an epoxy resin, if necessary (D) an inorganic filler, if necessary (E) a curing accelerator, if necessary (F) other additives, if necessary, and if necessary (G) an organic solvent to an arbitrary preparation vessel in any order and / or all or part of them at the same time and mixing them. In addition, the temperature can be appropriately set during the process of adding and mixing each component, and heating and / or cooling may be performed temporarily or throughout. In addition, during or after the process of adding and mixing, the resin composition may be stirred or shaken using a stirring device or shaking device such as a mixer to disperse uniformly. In addition, degassing may be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.

[0141] <Characteristics of resin composition> The resin composition of the present invention contains (A) a specific maleimide compound and (B) an active ester compound. By using such a resin composition, it is possible to obtain a cured product having a low relative dielectric constant (Dk) and dielectric loss tangent (Df), a high glass transition temperature (Tg), and excellent copper adhesion.

[0142] The cured product of the resin composition of the present invention may be characterized by a low dielectric loss tangent (Df). Thus, in one embodiment, the dielectric loss tangent (Df) of the cured product of the resin composition, as measured at 5.8 GHz and 23° C. as in Test Example 1 below, may be preferably 0.020 or less, 0.010 or less, more preferably 0.009 or less, 0.008 or less, even more preferably 0.007 or less, 0.006 or less, and particularly preferably 0.005 or less, 0.004 or less.

[0143] The cured product of the resin composition of the present invention may be characterized by a low dielectric constant (Dk). Thus, in one embodiment, the dielectric constant (Dk) of the cured product of the resin composition, as measured at 5.8 GHz and 23° C. as in Test Example 1 below, may be preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.5 or less, and particularly preferably 3.0 or less.

[0144] The cured product of the resin composition of the present invention may be characterized by a high glass transition temperature (Tg). Thus, in one embodiment, the glass transition temperature (Tg) measured as in Test Example 2 below may be preferably 120° C. or higher, more preferably 140° C. or higher, even more preferably 150° C. or higher, and particularly preferably 160° C. or higher.

[0145] The cured product of the resin composition of the present invention may have the characteristic of excellent copper adhesion. Thus, in one embodiment, the adhesion strength of the base copper (copper foil) measured according to JIS C6481 as in the following Test Example 5 may be preferably 0.2 kgf / cm or more, more preferably 0.3 kgf / cm or more, even more preferably 0.4 kgf / cm or more, and particularly preferably 0.5 kgf / cm or more. The upper limit is not particularly limited, but may be, for example, 10 kgf / cm or less. In one embodiment, as in the following Test Example 4, a copper plating conductor layer is formed on the cured product, and the copper plating peel strength calculated from the load when the copper plating conductor layer is peeled off in the vertical direction may be preferably 0.2 kgf / cm or more, more preferably 0.3 kgf / cm or more, even more preferably 0.35 kgf / cm or more, and particularly preferably 0.4 kgf / cm or more. The upper limit is not particularly limited, but may be, for example, 10 kgf / cm or less.

[0146] In one embodiment, the cured product of the resin composition of the present invention may be characterized by a low arithmetic mean roughness (Ra) of the surface after roughening treatment. Therefore, in one embodiment, the arithmetic mean roughness (Ra) of the cured product surface after roughening treatment measured as in the following Test Example 3 may be preferably 300 nm or less, more preferably 200 nm or less, even more preferably 170 nm or less, even more preferably 150 nm or less, and particularly preferably 130 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc.

[0147] <Applications of resin composition> The resin composition of the present invention can be suitably used as a resin composition for insulating purposes, particularly as a resin composition for forming an insulating layer. Specifically, it can be suitably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer for forming a conductor layer) for forming a conductor layer (including a rewiring layer) formed on an insulating layer. In addition, in a printed wiring board described later, it can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board). The resin composition of the present invention can also be used in a wide range of applications requiring a resin composition, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, and a component embedding resin.

[0148] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can be suitably used as a resin composition for a rewiring formation layer (resin composition for forming a rewiring formation layer) as an insulating layer for forming a rewiring layer, and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0149] Furthermore, the resin composition of the present invention provides an insulating layer with good component embedding properties, and therefore can be suitably used when the printed wiring board is a circuit board with built-in components.

[0150] <Sheet-type laminated material> The resin composition of the present invention can be used by coating in the form of a varnish, but from an industrial perspective, it is generally preferred to use the resin composition in the form of a sheet-like laminate material containing the resin composition.

[0151] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.

[0152] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed from the resin composition of the present invention.

[0153] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.

[0154] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0155] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0156] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0157] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0158] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0159] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0160] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0161] The resin sheet can be produced, for example, by preparing a liquid resin composition as is or a resin varnish by dissolving the resin composition in an organic solvent, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.

[0162] The organic solvent may be the same as the organic solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more kinds.

[0163] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the organic solvent in the resin composition layer becomes 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when a resin composition or resin varnish containing 30% by mass to 60% by mass of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0164] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0165] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition of the present invention.

[0166] The sheet-like fiber substrate used for the prepreg is not particularly limited, and can be a substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.

[0167] The prepreg can be produced by a known method such as a hot melt method or a solvent method.

[0168] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.

[0169] The sheet-like laminate material of the present invention can be suitably used for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).

[0170] <Printed wiring board> The printed wiring board of the present invention includes an insulating layer made of a cured product obtained by curing the resin composition of the present invention.

[0171] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., heat curing) the resin composition layer to form an insulating layer.

[0172] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0173] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0174] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0175] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0176] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0177] The support may be removed between step (I) and step (II) or after step (II).

[0178] In step (II), the resin composition layer is cured (for example, thermally cured) to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions that are usually adopted when forming an insulating layer for a printed wiring board may be used.

[0179] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0180] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0181] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in manufacturing printed wiring boards. When the support is removed after step (II), the support may be removed between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (II) to (V) may be repeated to form a multilayer wiring board, as necessary.

[0182] In another embodiment, the printed wiring board of the present invention can be manufactured using the above-mentioned prepreg. The manufacturing method is basically the same as when a resin sheet is used.

[0183] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0184] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0185] The swelling liquid used in the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, etc., and is preferably an alkaline solution, and more preferably a sodium hydroxide solution or a potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes, for example. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0186] The oxidizing agent used in the roughening treatment is not particularly limited, but examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0187] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product such as "Reduction Solution Securigant P" manufactured by Atotech Japan can be mentioned.

[0188] The treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.

[0189] In one embodiment, the root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0190] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0191] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0192] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0193] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0194] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0195] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.

[0196] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0197] <Semiconductor device> The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.

[0198] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES

[0199] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions are room temperature (23°C) and atmospheric pressure (1 atm).

[0200] <Example 1> 20 parts of an isophoronediamine skeleton-containing maleimide compound ("SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd., an anisole solution with a solid content of 50% by mass, main component (non-volatile component): a maleimide compound represented by the following formula (A)), 17.7 parts of an active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, a toluene solution with a solid content of 62% by mass), 18 parts of naphthol aralkyl type epoxy resin ("ESN-475V" manufactured by Nippon Steel Chemical & Material Co., Ltd.), and spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.). 2 A resin composition (resin varnish) was prepared by mixing 60 parts of a cellulose acetate copolymer (1-benzyl-2-phenylimidazole), 1 part of an imidazole curing accelerator ("1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-phenylimidazole), and 20 parts of methyl ethyl ketone and dispersing the mixture uniformly in a high-speed rotating mixer.

[0201] [ka]

[0202] <Example 2> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that the amount of the active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) used was changed from 17.7 parts to 16.1 parts, the amount of the naphthol aralkyl type epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-475V") used was changed from 18 parts to 15 parts, and 5.7 parts of a biphenyl aralkyl novolac type polymaleimide (Nippon Kayaku Co., Ltd.'s "MIR-3000-70MT", a MEK / toluene mixed solution with a solid content of 70%) was further used.

[0203] <Example 3> An MEK solution (70% by mass of non-volatile components) of maleimide compound A (Mw / Mn=1.81, t''=1.47 (mainly 1, 2 or 3)) represented by the following formula (1) synthesized by the method described in Synthesis Example 1 of the Japan Institute of Invention and Innovation Disclosure Technical Journal Publication No. 2020-500211 was prepared.

[0204] [ka]

[0205] A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that the amount of the active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) used was changed from 17.7 parts to 16.1 parts, the amount of the naphthol aralkyl epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-475V") used was changed from 18 parts to 15 parts, and 5.7 parts of maleimide compound A (MEK solution with a solid content of 70%) was further used.

[0206] <Example 4> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that the amount of the active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) used was changed from 17.7 parts to 16.1 parts, the amount of the naphthol aralkyl type epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-475V") used was changed from 18 parts to 15 parts, and 6.2 parts of a terminal vinyl benzylated PPE compound (Mitsubishi Gas Chemical Corporation's "OPE-2St 1200", a toluene mixed solution with a solid content of 65%) was further used.

[0207] <Example 5> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that the amount of the active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) used was changed from 17.7 parts to 16.1 parts, the amount of the naphthol aralkyl type epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-475V") used was changed from 18 parts to 15 parts, and 6.2 parts of a divinylbenzene / styrene copolymer (Nippon Steel Chemical & Material Corporation's "ODV-XET-X04", a toluene solution with a solid content of 65%) was further used.

[0208] <Example 6> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that the amount of the active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) used was changed from 17.7 parts to 16.1 parts, the amount of the naphthol aralkyl-type epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-475V") used was changed from 18 parts to 15 parts, and 8 parts of a terminal methacrylic modified PPE compound (Sabic Innovative Plastics Corporation's "SA9000-111", adjusted to a 50% solid content solution with toluene) were further used.

[0209] <Comparative Example 1> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that 10 parts of an aliphatic maleimide (Designer Molecules' "BMI-689") was used instead of 20 parts of an isophoronediamine skeleton-containing maleimide compound (Shin-Etsu Chemical Co., Ltd.'s "SLK-2600").

[0210] <Comparative Example 2> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that 14.3 parts of a biphenylaralkyl novolac type polymaleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., a MEK / toluene mixed solution with a solid content of 70%) was used instead of 20 parts of an isophoronediamine skeleton-containing maleimide compound ("SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd.).

[0211] <Comparative Example 3> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that 20 parts of the isophoronediamine skeleton-containing maleimide compound ("SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd.) was not used, the amount of the active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, a toluene solution with a solid content of 62% by mass) was changed from 17.7 parts to 25.8 parts, and the amount of the naphthol aralkyl-type epoxy resin ("ESN-475V" manufactured by Nippon Steel Chemical & Material Co., Ltd.) was changed from 18 parts to 23 parts.

[0212] <Comparative Example 4> A resin composition (resin varnish) was prepared in the same manner as in Example 1, except that 17.7 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", a toluene solution with a solid content of 62% by mass) was not used, the amount of spherical silica (Admatechs Corporation's "SO-C2") surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") was changed from 60 parts to 51 parts, and 8.3 parts of a phenol-based epoxy curing agent (DIC Corporation's "LA-7054", a MEK solution with a solid content of 60%) was further used.

[0213] <Test Example 1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin compositions obtained in the examples and comparative examples were uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet A including a support and a resin composition layer.

[0214] The obtained resin sheet A was cured for 90 minutes in an oven at 190° C. The support was peeled off from the resin sheet A taken out of the oven to obtain a cured product of the resin composition layer. The cured product was cut into a length of 80 mm and a width of 2 mm to be used as cured product B for evaluation.

[0215] The dielectric constant (Dk value) and dielectric tangent (Df value) of the cured product B for evaluation were measured by the cavity resonance perturbation method using an Agilent Technologies "HP8362B" at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. Measurements were performed on two test pieces, and the average was calculated.

[0216] <Test Example 2: Measurement of glass transition temperature (Tg)> Resin sheet A obtained in Test Example 1 was cured in an oven at 190°C for 90 minutes and then peeled off from the support to obtain a cured film. This cured film was cut into a length of 20 mm and a width of 6 mm to prepare an evaluation sample. The glass transition temperature (Tg) of this evaluation sample was measured at a heating rate of 5°C / min from 25°C to 250°C using a TMA device (thermomechanical analyzer) manufactured by Rigaku Corporation. The same test piece was measured twice, and the second value was recorded.

[0217] <Test Example 3: Measurement of arithmetic mean roughness (Ra)> (1) Preparation of inner layer board Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, Panasonic "R1515A") with an inner layer circuit formed were etched 1 μm with a microetching agent (Mec "CZ8101") to roughen the copper surface.

[0218] (2) Lamination of resin sheet A Using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.), the resin sheet A obtained in Test Example 1 was laminated on both sides of the inner layer substrate so that the resin composition layer was in contact with the inner layer substrate. The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, a heat press was performed at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0219] (3) Thermal curing of the resin composition layer Thereafter, the inner layer substrate laminated with the resin sheet A was placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes to thermally cure the resin composition layer and form an insulating layer. Thereafter, the support was peeled off to obtain a cured substrate A having the insulating layer, the inner layer substrate, and the insulating layer in this order.

[0220] (4) Roughening treatment A desmear treatment was carried out as a roughening treatment on the cured substrate A. The desmear treatment was the following wet desmear treatment.

[0221] (Wet desmear treatment) The cured substrate A was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 5 minutes, then immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 20 minutes, then immersed in a neutralizing solution (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of sulfuric acid) at 40°C for 5 minutes, and then dried at 80°C for 15 minutes.

[0222] (5) Measurement of the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment The arithmetic mean roughness (Ra) of the insulating layer surface of the cured substrate A after the roughening treatment was determined using a non-contact surface roughness meter (WYKO NT3300 manufactured by Bruker) in VSI mode with a 50x lens over a measurement range of 121 μm × 92 μm. The measurements were taken by calculating the average value of 10 points.

[0223] <Test Example 4: Measurement of copper plating peel strength> (1) Formation of copper-plated conductor layer According to the semi-additive method, a conductor layer was formed on the roughened surface of the insulating layer of the cured substrate A obtained in Test Example 3 after the roughening treatment. That is, the substrate after the roughening treatment was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. Next, after heating at 150°C for 30 minutes to perform an annealing treatment, an etching resist was formed, and a pattern was formed by etching. Then, copper sulfate electrolytic plating was performed to form a conductor layer having a thickness of 25 μm, and an annealing treatment was performed at 190°C for 60 minutes. The obtained substrate is called "evaluation substrate B".

[0224] (2) Measurement of peel strength of copper-plated conductor layer The peel strength of the insulating layer and the conductor layer was measured in accordance with the Japanese Industrial Standard (JIS C6481). Specifically, a cut was made in the conductor layer of evaluation board B, measuring 10 mm wide and 100 mm long, and one end of the cut was peeled off and held with a gripper. The load (kgf / cm) was measured when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature, and the peel strength was calculated. A tensile tester (TSE's "AC-50C-SL") was used for the measurement.

[0225] <Test Example 5: Measurement of adhesion strength of copper (copper foil) substrate> (1) Copper foil preparation The shiny side of Mitsui Mining & Smelting Co., Ltd.'s "3EC-III" (electrolytic copper foil, 35μm) was immersed in a micro-etching agent (Mec Co., Ltd.'s "CZ8101") to roughen the copper surface (Ra value = 1μm) and apply anti-rust treatment (CL8300). This copper foil is called CZ copper foil. It was then heated in an oven at 130℃ for 30 minutes.

[0226] (2) Lamination of copper foil and formation of insulating layer An inner layer substrate laminated with resin sheet A was prepared in the same manner as in Test Example 3. Then, the supports on both sides of the substrate were peeled off to expose both resin composition layers. The treated surface of the CZ copper foil of "3EC-III" was laminated on the resin composition layers under the same conditions as those for laminating resin sheet A in Test Example 1. Then, the resin composition layer was cured under curing conditions of 190°C and 90 minutes to form an insulating layer, thereby producing a sample.

[0227] (3) Measurement of copper foil peel strength (substrate adhesion) The prepared sample was cut into small pieces of 150 x 30 mm. A cutter was used to make a 10 mm wide and 100 mm long cut in the copper foil part of the small piece, and one end of the copper foil was peeled off and held with a gripper ("AC-50C-SL" manufactured by TSE Co., Ltd.). Using an Instron universal testing machine, the load [kgf / cm (N / cm)] when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured in accordance with JIS C6481.

[0228] The amounts of non-volatile components used in the resin compositions of the Examples and Comparative Examples, and the measurement results of the Test Examples are shown in Table 1 below.

[0229] [Table 1]

[0230] Referring to Table 1, in Comparative Examples 2 and 3 in which the specific maleimide compound (A) was not used, the copper foil adhesion was low, and the relative dielectric constant (Dk) and dielectric loss tangent (Df) were high. In Comparative Example 1 in which a maleimide compound having a dimer diamine skeleton was used instead of the specific maleimide compound (A), the glass transition point (Tg) was low. In Comparative Example 4 in which a phenolic curing agent was used instead of the active ester compound (B) as the epoxy curing agent, the relative dielectric constant (Dk) and dielectric loss tangent (Df) were very high. In contrast, it can be seen that these problems can be overcome when the resin composition of the present invention containing the specific maleimide compound (A) and the active ester compound (B) is used.

Claims

1. (A) Formula (A): 【Chemistry 1】 [In the formula, n1 represents an integer of 1 or more; n2 represents 0 or an integer of 1 or more; one of m1 and m2 represents 1 and the other represents 0; and there is a bond between the n1 unit and the n2 unit.] (A') another radical polymerizable compound, (B) an active ester compound, and (C) an epoxy resin, The component (A') contains a modified polystyrene resin having a vinylphenyl group, The content of the modified polystyrene resin having a vinylphenyl group is 0.1% by mass to 20% by mass, based on 100% by mass of the non-volatile components in the resin composition; The content of the (C) component is 10% by mass to 50% by mass, relative to 100% by mass of the non-volatile components in the resin composition; A resin composition, in which a mass ratio of the component (A) to the component (B) (content of the component (A) / content of the component (B)) is 0.7 to 3.

2. The resin composition according to claim 1, wherein the weight average molecular weight of the component (A) is 2,000 to 50,000.

3. 3. The resin composition according to claim 1, wherein the content of the component (A) is 3% by mass to 30% by mass, based on 100% by mass of non-volatile components in the resin composition.

4. The resin composition according to any one of claims 1 to 3, wherein the content of the component (B) is 3% by mass to 30% by mass, based on 100% by mass of non-volatile components in the resin composition.

5. The resin composition according to any one of claims 1 to 4, further comprising (D) an inorganic filler.

6. Further comprising (D) an inorganic filler, The resin composition according to any one of claims 1 to 3, wherein the content of the component (D) is 40 mass% or more, based on 100 mass% of non-volatile components in the resin composition.

7. Further comprising (D) an inorganic filler, The content of the (B) component is 3% by mass to 20% by mass, based on 100% by mass of the non-volatile components in the resin composition; The resin composition according to claim 4, wherein the content of the component (D) is 40% by mass or more, based on 100% by mass of non-volatile components in the resin composition.

8. The resin composition according to any one of claims 1 to 7, wherein the dielectric loss tangent (Df) of a cured product of the resin composition is 0.005 or less when measured at 5.8 GHz and 23 ° C.

9. The resin composition according to any one of claims 1 to 8, wherein the cured product of the resin composition has a relative dielectric constant (Dk) of 3.0 or less when measured at 5.8 GHz and 23°C.

10. The resin composition according to any one of claims 1 to 9, wherein the glass transition temperature (Tg) of a cured product of the resin composition is 150°C or higher.

11. A cured product of the resin composition according to any one of claims 1 to 10.

12. A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 10.

13. A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of claims 1 to 10 provided on the support.

14. A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of claims 1 to 10.

15. A semiconductor device comprising the printed wiring board according to claim 14.

Citation Information

Patent Citations

  • Thermosetting maleimide resin composition for sealing semiconductor, and semiconductor device

    JP2019203122A

  • Thermosetting maleimide resin composition, adhesive using the same, substrate material, primer, coating material and semiconductor device

    JP2021181531A

  • Resin material, laminate structure and multilayer printed wiring board

    WO2019189467A1